Singular case report of familial hypocalciuric hypercalcemia: a rare diagnosis of hypercalcemia in the older people - Etienne Ojardias; Mélanie Leman; Ludovic Lafaie; Philippe Oriol; Paul Calmels; Thomas Celarier (The Aging Male)
Objective to report a case of familial hypocalciuric hypercalcemia (FHH) in an older patient and highlight the diagnostic challenges in geriatric populations.Case presentation We report the diagnosis of FHH in an 88-year-old polypathological patient with hypercalcemia discovered during a check-up for cardiac decompensation. Despite a confusing clinical presentation with gout symptoms, including repeated episodes of knee arthritis, persistent hypercalcemia conducted further investigations. Biological tests excluded primary or hyperparathyroidism and malignancy-related hyperparathyroidism, confirming the diagnosis of FHH through the detection of an inhibitory mutation in the calcium-sensing receptor gene.Conclusion This case suggests to clinicians the possibility of FHH in older patients with unexplained hypercalcemia. In geriatric patients, the diagnosis is complicated because of the poly-pathology: here hypercalcemia was associated with a confusing gout crisis, which was triggered by diuretic treatment for heart failure.